Effect of planting materials and organic amendments on the production of purple passion fruit (Passiflora edulis Sims.) seedlings - Shahbani, Nur Shahirah; Ramaiya, Shiamala Devi; Saupi, Noorasmah; Bujang, Japar Sidik; Zakaria, Muta Harah (Pakistan Botanical Society, 2022)
The rising popularity of passion fruit (Passiflora edulis Sims) in the local and international markets is due to its nutraceutical and pharmaceutical application, which leads to economical opportunities for farmers in Malaysia and worldwide. The production of seedlings comprises crucial phases of the cultivation system through the selection of substrate and planting materials for the development of seedlings and plant conditions in the field. Accordingly, this research aims to the examine the effect of organic manures and planting materials used for purple passion fruit seedlings production. The pot experiment was design following the Randomized Complete Block Design (RCBD) with factorial arrangement 4 x 2 (4 types of substrates x 2 types of planting materials) with 6 replication per treatment. The Kaplan-Meier analysis recorded that softwood cutting had a higher seedling survival rate of 83% to 100% in comparison to semi-hardwood cutting, with a lower survival rate of 0% to 50%. Among the treatments, the substrates with rabbit composite and soil with softwood cutting (T1) exhibited more significant Dickson’s Quality Index, improving the original development of purple passion fruit seedlings as the leaves amounted to 24.67±1.45, stem diameter of 6.32±0.55 mm, and plant height of 139.33±8.29 cm. The fresh and dried aerial mass of 48.58±0.74 g and 11.51±0.38 g, respectively, including the root mass of 10.23±0.37 g and 2.13±0.35 g was enhanced through the treatment. Notably, the composition of organic rabbit composite and softwood cutting improved the cultivation and feasibility of the passion fruit seedlings.